Psychometric Properties of the Violence-Related Attitudes and Beliefs Scale (VRA). - Lúcar Vidal, Fredrik (2013)
This paper’s main purpose was to translate the Violence-Related Attitudes and Beliefs Scale (V-RABS) into Spanish, carry out the appropriate linguistic adjustment, and then assess the psychometric properties of this questionnaire for a sample of 505 degree students aged 16 - 37 (M = 21.48). The the content and the construct validity and reliability were assessed. Results showed that the content of the questionnaire is valid and the factorial structure reproduced the same structure proposed in the original study. Likewise, the internal consistency was acceptable. In light of the obtained results, this translated version into Spanish can be considered valid and reliable for the assessment of attitudes and beliefs about the causes and control of violence and crime.